EFFICACY OF GREEN SYNTHESIZED SILVER NANOPARTICLES AGAINST LATE LEAF SPOT DISEASE IN GROUNDNUT CAUSED BY PHAEOISARIOPSIS PERSONATA (Journal of Plant Disease Sciences, 2026)
Groundnut ( L.) is one of India’s most important oilseed crops, extensively cultivated under tropical and subtropical conditions. Productivity is frequently constrained by foliar fungal diseases, particularly late leaf spot (LLS)caused by . Under conducive environmental conditions such as prolonged leaf wetness, high humidity and moderate temperatures-the disease can induce defoliation, weaken haulm quality and cause pod yield losses exceeding 50–70%. Chemical fungicides remain the dominant management tool; however, issues such as environmental contamination, pathogen resistance and residue hazards justify the search for eco-friendly alternatives. Nanotechnology provides a novel opportunity for disease control due to the unique physicochemical properties of nanoparticles. This investigation focused on optimization of dose through poisoned food technique and its field efficacyunder Kharif conditions at Central Campus, MPKV Rahuri. Biosynthesized AgNPs exhibited reddish-brown coloration with UV-Vis absorption around 430–450 nm, indicative of spherical crystalline structures. Transmission Electron Microscopy (TEM) revealed particle sizes predominantly ranging between 20–60 nm. assays demonstrated significant mycelial inhibition at 100, 125 and 150 ppmconcentrations. Field application of 150 ppm AgNPs recorded the lowest disease severity and was statistically comparable to mancozeb and carbendazim. These findings highlight the potential of green nanomaterials as safer alternatives to fungicidesfor sustainable groundnut production.
Keywords: Groundnut; Late leaf spot; Nanoparticles; Ocimum sanctum; Phaeoisariopsis personata